Experimental and numerical behavior of anisotropic laminated FRP thin-walled web beams under different loading and boundary parameters - Sharma, Garima (Kansas State University, 2022)
Structural elements made of fibrous composites are increasingly used in aerospace, automotive, civil and marine engineering applications due to their high stiffness and strength-to-weight ratio and corrosion resistance properties. Most of the composite structural elements are thin-walled and their design is often controlled by stability considerations mainly due to slenderness effects. Hence, for thin-walled slender composite beams, lateral torsional buckling (LTB) is the dominant failure mode regardless of the fiber orientations. In this study, combined numerical and experimental investigations for lateral torsional buckling of laminated composite web-cantilever and simply support beams are presented. A total of twelve carbon-fiber beams with six different anisotropic layups having a nominal length to height (𝑙/ℎ) ratio of 10 and four glass-fiber reinforced polymer beams with varying 𝑙/ℎ ratios were experimentally tested for cantilever and simply support conditions respectively. The experimental response is compared against a non-linear numerical solution using Static Riks Analysis (SRA) to compare the predicted vs. actual load-displacement curve. An analytical approach, developed in an earlier study, was used to find the critical buckling load. Eigen value analysis was performed to benchmark the analytical buckling load using Abaqus.
Keywords: Fiber reinforced polymers; Anisotropic